Separator for electrochemical device and electrochemical device including the same

By setting up a silicon -based negative adhesive layer in the partition parts of the electrochemical device, and using a polyacrylamide -based adhesive in the adhesive layer and negative electrode, the electrochemical device is solved The stability and life problem caused by expansion achieve higher adhesion strength and stability.

CN119384767APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003009.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-21
Filing Date
2024-04-08
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When using the silicon-based negative electrode, the existing electrochemical device has problems with volume expansion due to charging and discharging, resulting in deterioration of the stability and lifetime characteristics of the electrochemical device.

Method used

A separators for electrochemical devices are designed, and the adhesive layer is set to a silicon -oriented negative electrode, and each contains a polyacrylamide -based adhesive in the adhesive layer and negative electrode to improve the adhesion Combine strength and inhibit swelling.

Benefits of technology

By improving the bonding strength of the negative electrode with silicon -based, the stability and life characteristics of the electrochemical device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384767A_ABST
    Figure CN119384767A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same, and more specifically, to a separator for an electrochemical device, the present invention relates to a separator for an electrochemical device and an electrochemical device comprising the same, and more particularly, to a separator for an electrochemical device and an electrochemical device comprising the same, in which a binder layer is provided to face a silicon-based negative electrode and the silicon-based negative electrode and the binder layer each contain a polyacrylamide (PAM)-based binder, and thus, it is possible to improve the adhesive strength with the silicon-based negative electrode, swelling of an electrochemical device to which a silicon-based negative electrode is applied can be suppressed to improve the stability of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure claims the priority of Korean Patent Application No. 10-2023-0052786 filed on April 21, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the same, and more particularly, to a separator for an electrochemical device and an electrochemical device including the same, wherein an adhesive layer is arranged to face a silicon-based negative electrode and the silicon-based negative electrode and the adhesive layer each contain a polyacrylamide (PAM)-based binder, thereby the bonding strength with the silicon-based negative electrode can be improved, and the swelling of the electrochemical device to which the silicon-based negative electrode is applied can be suppressed to improve the stability of the electrochemical device. Background Art

[0003] In the components of electrochemical devices, the separator includes a polymer substrate with a porous structure, which is located between the positive electrode and the negative electrode and is used to isolate the positive electrode and the negative electrode, prevent electrical short circuits between the two electrodes, and allow electrolytes and ions to pass through it. The separator itself does not participate in the electrochemical reaction, but physical properties such as wettability to the electrolyte solution, porosity, and thermal shrinkage affect the performance and safety of the electrochemical device.

[0004] Therefore, in order to enhance the physical properties of the separator, various methods have been tried to add a coating to a porous polymer substrate and to change the physical properties of the coating by adding various materials to the coating. For example, an inorganic material can be added to the coating to increase the mechanical strength of the separator, or an inorganic material or hydrate can be added to the coating to improve the flame retardancy and heat resistance of the polymer substrate.

[0005] The separator may be combined with the electrode through a lamination process, and in order to ensure adhesive strength between the electrode and the separator, a binder resin may be added to the coating composition of the separator.

[0006] Meanwhile, among negative electrode active materials used in negative electrodes of electrochemical devices, silicon-based active materials have attracted attention due to their capacity, which is about 10 times higher than that of carbon-based active materials, and due to the high capacity, high energy density can be achieved even with thin electrodes. However, there is a problem that the volume of silicon-based active materials expands due to charge and discharge, resulting in deterioration of life characteristics.

[0007] Therefore, there is a need for research on a separator in which the bonding strength with the silicon-based negative electrode can be improved and the stability of the electrochemical device can be improved by suppressing the swelling of the electrochemical device to which the silicon-based negative electrode is applied. Summary of the invention

[0008] Technical problem

[0009] The present disclosure aims to provide a separator for an electrochemical device and an electrochemical device including the same, in which an adhesive layer is disposed to face a silicon-based negative electrode, and both the silicon-based negative electrode and the adhesive layer each include a polyacrylamide (PAM)-based binder, so that the adhesion strength to the silicon-based negative electrode can be improved, and swelling of the electrochemical device using the silicon-based negative electrode can be suppressed to improve the stability of the electrochemical device.

[0010] However, the object of the present disclosure is not limited to the above object, and those skilled in the art will be able to clearly understand other objects not mentioned from the following description.

[0011] Technical solution

[0012] An embodiment of the present disclosure provides a separator for an electrochemical device, including an adhesive layer disposed to face a silicon-based negative electrode, wherein the silicon-based negative electrode includes a silicon-based negative electrode active material and a first polymer binder, the adhesive layer includes a second polymer binder, and both the first polymer binder and the second polymer binder are polyacrylamide (PAM)-based binders.

[0013] According to an embodiment of the present disclosure, the content of the first polymer binder may be 12 parts by weight or less relative to 100 parts by weight of the silicon-based negative electrode.

[0014] According to an embodiment of the present disclosure, the content of the second polymer binder may be 50 parts by weight or less relative to 100 parts by weight of the adhesive layer.

[0015] According to an embodiment of the present disclosure, the silicon-based negative electrode active material may be one or more selected from Si, SiO x (0 < x < 2), Si-Y alloy, and Si-C composite material, and Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, and may not be Si.

[0016] According to an embodiment of the present disclosure, the separator may include a porous polymer substrate, a coating disposed on at least one surface of the porous polymer substrate, and an adhesive layer disposed between the silicon-based negative electrode and the coating.

[0017] According to an embodiment of the present disclosure, the coating may include inorganic particles and a third polymer binder.

[0018] According to an embodiment of the present disclosure, the average particle size D50 of the inorganic particles may be in the range of 0.3 μm or more and 1.0 μm or less.

[0019] According to one embodiment of the present disclosure, the third polymer binder may be an acrylic-based binder, a polyvinylidene-based binder, or a combination thereof.

[0020] According to one embodiment of the present disclosure, the dry adhesive strength of the adhesive layer may be 50 gf / 25 mm or more.

[0021] According to one embodiment of the present disclosure, the wet adhesive strength of the adhesive layer may be in the range of 10 gf / 25 mm or more and 30 gf / 25 mm or less.

[0022] One embodiment of the present disclosure provides an electrochemical device including a positive electrode, a silicon-based negative electrode, and a separator interposed between the positive electrode and the silicon-based negative electrode.

[0023] Beneficial Effects

[0024] According to the separator for an electrochemical device according to one embodiment of the present disclosure, the bonding strength with the silicon-based negative electrode may be improved.

[0025] According to the separator for an electrochemical device according to one embodiment of the present disclosure, swelling of an electrochemical device to which a silicon-based negative electrode is applied may be suppressed, thereby improving the stability of the electrochemical device. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic diagram of a separator for an electrochemical device according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0027] In the present specification, when a certain part is described as “including” a certain element, unless specifically described otherwise, it means that the certain part may further include other elements, rather than excluding other elements.

[0028] In the present specification, the term "A and / or B" means "A and B or A or B".

[0029] In the present specification, when a component is described as being disposed 'on' a component, unless specifically described otherwise, it means that other components may be further disposed, and does not exclude that other components are disposed therebetween.

[0030] In this specification, the feature of “having pores” means that the object includes a plurality of pores and gas and / or liquid fluid can pass through the pores from one surface of the object to the other surface through a structure in which the pores are interconnected.

[0031] In this specification, a "separator" has a porous property including a large number of pores and serves as a porous ion-conducting barrier that allows ions to pass therethrough while preventing electrical contact between a negative electrode and a positive electrode in an electrochemical device.

[0032] Hereinafter, the present disclosure will be described in more detail.

[0033] One embodiment of the present disclosure provides a separator for an electrochemical device, comprising an adhesive layer disposed to face a silicon-based negative electrode, wherein the silicon-based negative electrode comprises a silicon-based negative electrode active material and a first polymer binder, the adhesive layer comprises a second polymer binder, and the first polymer binder and the second polymer binder are polyacrylamide (PAM)-based binders.

[0034] According to the separator for an electrochemical device according to one embodiment of the present disclosure, the bonding strength with the silicon-based negative electrode can be improved. In addition, according to the separator for an electrochemical device according to one embodiment of the present disclosure, the swelling of the electrochemical device to which the silicon-based negative electrode is applied can be suppressed, thereby improving the stability of the electrochemical device.

[0035] Figure 1 Schematic diagram of a separator for an electrochemical device according to one embodiment of the present disclosure. Figure 1 , the separator 100 for an electrochemical device according to one embodiment of the present disclosure will be described in detail.

[0036] According to one embodiment of the present disclosure, an electrochemical device includes a silicon-based negative electrode. Among the negative electrode active materials used in the negative electrode of the electrochemical device, the silicon-based active material has a capacity that is about 10 times higher than that of the carbon-based active material, and therefore has an advantage of achieving high energy density even with a thin electrode due to the high capacity. However, since the silicon-based active material has a volume expansion problem caused by charging and discharging, the present disclosure is designed to solve such a problem.

[0037] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device includes an adhesive layer 150 disposed to face the silicon-based negative electrode. Specifically, the adhesive layer 150 may be bonded to the silicon-based negative electrode or located between the silicon-based negative electrode and the coating layer 130 or the porous polymer substrate 110 of the separator. As described above, since the separator for an electrochemical device may include an adhesive layer disposed to face the silicon-based negative electrode, the bonding strength with the silicon-based negative electrode may be improved, and the swelling of the electrochemical device to which the silicon-based negative electrode is applied may be suppressed, thereby improving the stability of the electrochemical device.

[0038] According to one embodiment of the present disclosure, the silicon-based negative electrode includes a silicon-based negative electrode active material and a first polymer binder. As described above, since the silicon-based negative electrode includes a silicon-based negative electrode active material and a first polymer binder, the electrode adhesion strength can be improved while minimizing the volume expansion and / or shrinkage of the silicon-based negative electrode active material to a sufficient extent.

[0039] According to one embodiment of the present disclosure, the silicon-based negative electrode includes a silicon-based negative electrode active material. Specifically, the silicon-based negative electrode may include a silicon-based compound as the silicon-based negative electrode active material. Non-limiting examples of the silicon-based compound may include Si, SiO x (0 < x < 2), Si-Y (Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element, or a combination thereof, and is not Si) alloy, and Si-C composite material, and includes one or both or more of them.

[0040] According to one embodiment of the present disclosure, the silicon-based negative electrode includes a first polymer binder. As described above, since the silicon-based negative electrode includes a first polymer binder, the adhesion strength to the separator can be improved by interacting with the second polymer binder included in the adhesive layer.

[0041] According to one embodiment of the present disclosure, the adhesive layer 150 includes a second polymer binder. As described above, when the adhesive layer includes a second polymer binder, the adhesion strength to the silicon-based negative electrode can be improved by interacting with the first polymer binder.

[0042] According to one embodiment of the present disclosure, each of the first polymer binder and the second polymer binder is a polyacrylamide (PAM)-based binder. Specifically, the polyacrylamide (PAM)-based binder may be derived from one or more monomers selected from acrylamide, N-hydroxymethylacrylamide, N-butoxymethylacrylamide, methacrylamide, N-hydroxymethylmethacrylamide, and N-butoxymethylmethacrylamide. By using the polyacrylamide (PAM)-based binder as the first polymer binder and the second polymer binder, the adhesion strength can be improved with stronger stress through hydrogen bonding or covalent bonding between the silicon-based negative electrode and the adhesive layer, and the volume expansion and / or shrinkage of the silicon-based negative electrode active material can be minimized to a sufficient extent.

[0043] According to one embodiment of the present disclosure, each of the first polymer binder and the second polymer binder may further include an aqueous binder. More specifically, the aqueous binder may include one selected from polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), and copolymers thereof. As described above, since each of the first polymer binder and the second polymer binder further includes an aqueous binder, the bonding strength can be increased with stronger stress through hydrogen bonding or covalent bonding between the silicon-based negative electrode and the adhesive layer.

[0044] According to one embodiment of the present disclosure, the content of the first polymer binder may be 12 parts by weight or less relative to 100 parts by weight of the silicon-based negative electrode. Specifically, the content of the first polymer binder may be 7 parts by weight or more and 12 parts by weight or less, 7.5 parts by weight or more and 11.5 parts by weight or less, 8 parts by weight or more and 11 parts by weight or less, 8.5 parts by weight or more and 10.5 parts by weight or less, or 9 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the silicon-based negative electrode. By adjusting the content of the first polymer binder within the above range, the electrode bonding strength can be increased while minimizing the volume expansion and / or contraction of the silicon-based negative electrode active material sufficiently.

[0045] According to one embodiment of the present disclosure, the content of the second polymer binder may be 50 parts by weight or less relative to 100 parts by weight of the adhesive layer. Specifically, the content of the second polymer binder may be 40 parts by weight or more and 50 parts by weight or less, 41 parts by weight or more and 49 parts by weight or less, 42 parts by weight or more and 48 parts by weight or less, 43 parts by weight or more and 47 parts by weight or less, or 44 parts by weight or more and 46 parts by weight or less relative to 100 parts by weight of the adhesive layer. By adjusting the content of the second polymer binder within the above range, the bonding strength with the silicon-based negative electrode can be increased.

[0046] According to one embodiment of the present disclosure, the silicon-based negative electrode active material may be one or more selected from Si, SiO x (0 < x < 2), Si-Y alloy, and Si-C composite material, where Y is an alkali metal, alkaline earth metal, Group 13 element, Group 14 element, transition metal, rare earth element, or a combination thereof, and may not be Si. Specifically, when the negative electrode contains the silicon-based negative electrode active material, the energy density and fast charging performance can be improved.

[0047] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device may include a porous polymer substrate 110, a coating 130 disposed on at least one surface of the porous polymer substrate, and an adhesive layer 150 disposed between a silicon-based negative electrode and the coating. As described above, since the separator for an electrochemical device may include a porous polymer and a coating to allow lithium ions to pass therethrough while preventing electrical contact, heat resistance and mechanical properties may be improved. In addition, since the separator for an electrochemical device may include an adhesive layer disposed between a silicon-based negative electrode and the coating, the bonding strength with the silicon-based negative electrode may be improved.

[0048] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device may include a porous polymer substrate 110 and an adhesive layer 150 disposed between a silicon-based negative electrode and the porous polymer substrate. Specifically, when the coating layer is not provided or the coating layer is provided only on one surface of the porous polymer substrate, as described above, by including the porous polymer substrate and the adhesive layer disposed between the silicon-based negative electrode and the porous polymer substrate, the bonding strength with the silicon-based negative electrode can be improved.

[0049] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device may include a porous polymer substrate 110. As described above, since the separator for an electrochemical device includes a porous polymer substrate to allow lithium ions to pass therethrough while blocking electrical contact, a shutdown function may be achieved at an appropriate temperature.

[0050] According to one embodiment of the present disclosure, the porous polymer substrate may include a polyolefin-based resin. Specifically, the porous polymer substrate may be manufactured using a polyolefin-based resin as a base resin. More specifically, examples of polyolefin-based resins may include polyethylene, polypropylene, polypentene, etc., and include one or more of them. A separator with porosity (i.e., a large number of pores) manufactured using such a polyolefin-based resin as a base resin may provide a shutoff function at an appropriate temperature.

[0051] According to one embodiment of the present disclosure, the weight average molecular weight of the polyolefin-based resin may be in the range of 500,000 or more and 1,500,000 or less. By adjusting the weight average molecular weight of the polyolefin-based resin within the above range, the compression resistance of the separator may be improved. In addition, when a mixture of different polyolefin-based resins is used or a separator having a multilayer structure made of different polyolefin-based resins is formed, the weight average molecular weight of the polyolefin-based resin may be calculated by adding the weight average molecular weights according to the content ratio of each polyolefin-based resin.

[0052] In the present specification, the "weight average molecular weight (Mw)" can be measured using gel permeation chromatography (PL GPC220, Agilent Technologies), and the measurement conditions can be set as follows.

[0053] - Column: PL Olexis (from Polymer Laboratories)

[0054] -Solvent: Trichlorobenzene (TCB)

[0055] -Flow rate 1.0ml / min

[0056] -Sample concentration 1.0mg / ml

[0057] -Injection volume 200μl

[0058] - Column temperature 160℃

[0059] -Detector: Agilent high temperature RI detector

[0060] -Standard: Polystyrene (calibrated by cubic function)

[0061] According to one embodiment of the present disclosure, the porous polymer substrate can be manufactured by a dry process or a wet process. Specifically, the porous polymer substrate can be manufactured by stretching a film made of a polyolefin-based resin in one direction and then stretching the stretched film in a direction perpendicular to the one direction (dry process). Alternatively, the porous polymer substrate can be manufactured by mixing a polyolefin-based resin with a diluent at high temperature to form a single phase, separating the polymer material and the diluent during cooling, then extracting the diluent to form pores, and then stretching and heat setting (wet process).

[0062] According to one embodiment of the present disclosure, by adjusting the mixing ratio of the diluent, the stretching ratio, the heat setting treatment temperature, etc., the average size and the maximum pore size of the porous polymer substrate can be easily adjusted to be included in the scope of the present disclosure.

[0063] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device may include a coating 130 disposed on at least one surface of a porous polymer substrate 110. Specifically, the separator for an electrochemical device includes a coating disposed on one surface or both surfaces of the porous polymer substrate. As described above, since the separator for an electrochemical device may include a coating disposed on at least one surface of the porous polymer substrate, the heat resistance and mechanical properties of the separator may be improved, and electrical short circuits of electrodes may be prevented from occurring due to shrinking the separator at high temperatures.

[0064] According to one embodiment of the present disclosure, the coating layer may include inorganic particles and a third polymer binder. As described above, since the coating layer includes inorganic particles and a third polymer binder, the heat resistance and mechanical properties of the separator can be improved, and electrical short circuits of the electrodes due to shrinkage of the separator at high temperatures can be prevented.

[0065] According to one embodiment of the present disclosure, the content of the third polymer binder in the coating layer may be 10 parts by weight or less. Specifically, relative to 100 parts by weight of the coating layer, the content of the third polymer binder may be greater than 0 parts by weight and 10 parts by weight or less, 1 part by weight or more and 9 parts by weight or less, 2 parts by weight or more and 8 parts by weight or less, 3 parts by weight or more and 7 parts by weight or less, or 4 parts by weight or more and 6 parts by weight or less. By adjusting the content of the third polymer binder within the above range to maintain the porosity of the separator, the bonding strength can be maintained even when the coating layer is wetted by the electrolyte solution after activation of the battery.

[0066] According to one embodiment of the present disclosure, the coating may include a plurality of pores. Specifically, the coating may be a porous coating. More specifically, the coating may be a porous coating including a plurality of pores therein. As described above, the coating includes a plurality of pores to allow lithium ions to pass through the pores and allow current to flow therethrough while physically blocking the negative electrode and the positive electrode.

[0067] According to one embodiment of the present disclosure, the inorganic particles are bound by a third polymer binder and integrated in a layer to form a coating. The pores inside the coating may be generated by the interstitial volume, which is the empty space between the inorganic particles.

[0068] According to one embodiment of the present disclosure, the coating layer may be formed at either side of the porous polymer substrate to have a thickness of 1 μm to 20 μm, but is not particularly limited thereto. The thickness may be adjusted to a suitable range by those skilled in the art in view of heat resistance or electrical resistance.

[0069] In one embodiment of the present disclosure, the thickness of the polymer substrate, coating and / or separator can be measured using a contact-type thickness gauge. For example, as a contact-type thickness gauge, VL-50S-B from Mitutoyo can be used.

[0070] According to one embodiment of the present disclosure, the inorganic particles that can be used in the coating are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in one embodiment of the present disclosure are not particularly limited thereto as long as no oxidation and / or reduction reaction occurs within the operating voltage range (e.g., 0V to 5V based on Li / Li+).

[0071] According to one embodiment of the present disclosure, non-limiting examples of inorganic particles may include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT,0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium oxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), zeolite-based compounds, etc., and may include one or two or more of them.

[0072] According to one embodiment of the present disclosure, the average particle size D50 of the inorganic particles can be within the range of 0.3 μm or more and 1.0 μm or less. Specifically, the average particle size D50 of the inorganic particles can be within the range of 0.4 μm or more and 0.9 μm or less, 0.5 μm or more and 0.8 μm or less, or 0.6 μm or more and 0.7 μm or less. By adjusting the average particle size D50 of the inorganic particles within the above range, in the slurry for coating (which is an emulsion containing the third polymer binder particles dispersed in water), the phase separation rate and phase separation efficiency between the third polymer binder particles and the inorganic particles can be improved. In addition, when the average particle size D50 of the inorganic particles is less than 0.3 μm, the dispersibility of the inorganic particles in the slurry for coating provided as a slurry for manufacturing the coating may be reduced, and when the average particle size D50 of the inorganic particles exceeds 1 μm, the thickness of the coating to be formed may be increased.

[0073] In this specification, "particle size D50" means the particle size at the 50% point of the cumulative distribution of the number of particles according to the particle size. The particle size can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particle passes through the laser beam, and the particle size is calculated thereby. The particle size D50 can be measured by calculating the particle size at the point where the cumulative distribution of the number of particles according to the particle size is 50% in the measuring device.

[0074] According to one embodiment of the present disclosure, the third polymer binder in the coating can be granular or non-granular. Specifically, as will be described below, the third polymer binder can maintain a particle shape without being dissolved by a dispersion medium or solvent, and the third polymer binder can be dissolved in a dispersion medium or solvent and can not maintain a particle shape. As described above, the mechanical properties and porosity of the coating can be adjusted by selecting a granular or non-granular third polymer binder.

[0075] According to one embodiment of the present disclosure, the average particle size D50 of the third particulate polymer binder is 1.0 μm or less. Specifically, the average particle size D50 of the third particulate polymer binder may be within the following ranges: 0.10 μm or more and 0.90 μm or less, 0.15 μm or more and 0.85 μm or less, 0.20 μm or more and 0.70 μm or less, 0.25 μm or more and 0.65 μm or less, or 0.30 μm or more and 0.50 μm or less. By adjusting the average particle size D50 of the third particulate polymer binder within the above range, in the slurry for coating (which is an emulsion containing the third particulate polymer binder dispersed in water), the phase separation rate and phase separation efficiency between the particulate third polymer binder and the inorganic particles can be improved.

[0076] According to one embodiment of the present disclosure, the third polymer binder may include one or more polymer binders. As described above, since the third polymer binder includes one or more polymer binders, the bonding strength of the coating can be improved, the porosity of the coating can be improved, and the dry bonding strength before the electrolyte solution is injected and the wet bonding strength after the electrolyte solution is injected can be improved at the same time.

[0077] According to one embodiment of the present disclosure, the third polymer binder may be an acrylic-based binder, a polyvinylidene-based binder, or a combination thereof. As described above, by using an acrylic-based binder, a polyvinylidene-based binder, or a combination thereof as the third polymer binder, the porosity of the separator may be maintained and the bonding strength may be maintained even when the coating is wetted by the electrolyte solution after activation of the battery.

[0078] According to one embodiment of the present disclosure, the third polymer binder may be an acrylic-based binder. By using an acrylic-based binder as the third polymer binder, the porosity of the separator can be maintained, the bonding strength between the electrode and the separator can be increased during the battery lamination process to easily manufacture the battery, and the stacking process can be stably achieved.

[0079] According to one embodiment of the present disclosure, the acrylic-based binder may be a polymer including carboxylic acid ester as a repeating unit, and may be preferably (meth)acrylic acid ester or acrylic acid-styrene copolymer.

[0080] According to one embodiment of the present disclosure, specific examples of (meth)acrylates may include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane (meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, ethylene di(meth)acrylate, and the like, and may be one or more selected from these. Among them, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and methyl (meth)acrylate is particularly preferred.

[0081] According to one embodiment of the present disclosure, the acrylic acid-styrene copolymer may include an acrylic acid-based binder, and the acrylic acid-based binder may be a polyacrylate-based binder. For example, the binder may be one or more selected from styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and an acrylate-based polymer, and specifically, may be a copolymer containing acrylate.

[0082] According to one embodiment of the present disclosure, the third polymer binder may be a polyvinylidene-based binder. Specifically, according to one embodiment of the present disclosure, the polyvinylidene-based binder may be a copolymer of polyvinylidene fluoride and hexafluoropropylene. As described above, by selecting the binder resin as a polyvinylidene-based binder, even when the coating is wetted by the electrolyte solution after activation of the battery, the adhesive strength may be maintained. In addition, the rigidity of the battery may be increased and the bending of the separator may be prevented.

[0083] According to one embodiment of the present disclosure, the polyvinylidene-based binder may be a water-based binder. Specifically, by selecting the polyvinylidene-based binder as the water-based binder, pollutants discharged during the manufacturing process of the separator may be minimized, thereby reducing the manufacturing cost of the battery.

[0084] According to one embodiment of the present disclosure, the third polymer binder may be a polyvinylidene-based binder having a hexafluoropropylene content of 1 wt % or more and 50 wt % or less. As described above, by selecting the third polymer binder as a polyvinylidene-based binder having a hexafluoropropylene content of 1 wt % or more and 50 wt % or less, the porosity of the separator may be maintained and the bonding strength may be maintained even when the coating is wetted by the electrolyte solution after activation of the battery.

[0085] According to one embodiment of the present disclosure, the porosity of the coating can be 30 volume % or more. Specifically, the porosity of the coating can be in the following range: 30 volume % or more and 70 volume % or less, 32 volume % or more and 68 volume % or less, 34 volume % or more and 66 volume % or less, 36 volume % or more and 64 volume % or less, 38 volume % or more and 62 volume % or less, 40 volume % or more and 60 volume % or less, 42 volume % or more and 58 volume % or less, 44 volume % or more and 56 volume % or less, 46 volume % or more and 54 volume % or less, or 48 volume % or more and 52 volume % or less. By adjusting the porosity of the coating within the above range, the movement of ions in the separator can be maintained, and the resistance of the separator is prevented from increasing. Specifically, when the porosity is 70 volume % or less, it is possible to ensure that the mechanical properties of the pressing process combined with the electrode can be withstood, and the surface opening rate is not too high, so that it is suitable for ensuring bonding strength. Meanwhile, when the porosity is 30 volume % or more, it is advantageous from the viewpoint of ion permeability.

[0086] In this specification, "porosity" means the ratio of the volume of pores to the total volume, uses volume % as a unit, and may be used interchangeably with terms such as porosity and porosity.

[0087] In this specification, the porosity corresponds to a value obtained by subtracting a volume calculated from the weight and density of each component of the coating from a volume calculated from the thickness, width, and length of the coating.

[0088] In one embodiment of the present disclosure, the porosity and pore size of the coating can be measured by the BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porosimeter, or a porosity analyzer (Bell Japan Inc, Belsorp-II mini). In this case, the use of a capillary flow porosimeter may be advantageous.

[0089] According to one embodiment of the present disclosure, the separator 100 for an electrochemical device may include an adhesive layer 150 disposed between the silicon-based negative electrode and the coating layer 130. As described above, since the separator for an electrochemical device may include an adhesive layer disposed between the silicon-based negative electrode and the coating layer, the bonding strength with the silicon-based negative electrode may be improved, and swelling of an electrochemical device to which the silicon-based negative electrode is applied may be suppressed, thereby improving the stability of the electrochemical device.

[0090] According to one embodiment of the present disclosure, the adhesive layer includes a second polymer binder. The content of the second polymer binder in the adhesive layer can be 50 parts by weight or less. Specifically, relative to 100 parts by weight of the adhesive layer, the content of the second polymer binder can be 40 parts by weight or more and 50 parts by weight or less, 41 parts by weight or more and 49 parts by weight or less, 42 parts by weight or more and 48 parts by weight or less, 43 parts by weight or more and 47 parts by weight or less, or 44 parts by weight or more and 46 parts by weight or less. By adjusting the content of the second polymer binder within the above range, the bonding strength with the negative electrode based on silicon can be improved.

[0091] According to one embodiment of the present disclosure, at the side of the coating layer in contact with the porous polymer substrate and at the other side, the thickness of the adhesive layer may be in the range of 1 μm to 20 μm, but is not particularly limited thereto. The thickness may be adjusted to a suitable range by those skilled in the art in view of the bonding strength with the electrode.

[0092] In one embodiment of the present disclosure, the thickness of the adhesive layer can be measured by using a contact-type thickness gauge. For example, as a contact-type thickness gauge, VL-50S-B from Mitutoyo can be used.

[0093] In the present specification, "wet adhesive strength" may refer to adhesive strength in a state where an electrolyte solution is injected into a battery, and "dry adhesive strength" refers to adhesive strength in a state before an electrolyte is injected into a battery.

[0094] According to one embodiment of the present disclosure, the dry bonding strength of the adhesive layer can be 50gf / 25mm or more. Specifically, the dry bonding strength of the adhesive layer can be in the following range: 50gf / 25mm or more and 150gf / 25mm or less, 60gf / 25mm or more and 140gf / 25mm or less, 70gf / 25mm or more and 130gf / 25mm or less, 80gf / 25mm or more and 120gf / 25mm or less, or 90gf / 25mm or more and 110gf / 25mm or less. By adjusting the dry bonding strength of the adhesive layer within the above range, the swelling of the electrochemical device to which the negative electrode based on silicon is applied can be suppressed, thereby improving the stability of the electrochemical device.

[0095] According to one embodiment of the present disclosure, the wet bonding strength of the adhesive layer can be within the range of 10gf / 25mm or more and 30gf / 25mm or less. Specifically, the wet bonding strength of the adhesive layer can be within the range of 12gf / 25mm or more and 28gf / 25mm or less, 14gf / 25mm or more and 26gf / 25mm or less, 16gf / 25mm or more and 24gf / 25mm or less, or 18gf / 25mm or more and 22gf / 25mm or less. By adjusting the wet bonding strength of the adhesive layer within the above range, the swelling of the electrochemical device to which the silicon-based negative electrode is applied can be suppressed, thereby improving the stability of the electrochemical device.

[0096] One embodiment of the present disclosure provides a method for manufacturing a separator for an electrochemical device, comprising mixing a slurry for a coating layer comprising a third polymer binder and inorganic particles (S10), providing a coating layer by applying the slurry for a coating layer on at least one surface of a porous polymer substrate and drying the slurry (S30), mixing a slurry for an adhesive layer comprising a second polymer binder (S50), and providing an adhesive layer by applying the slurry for an adhesive layer on one surface of the coating layer and drying the slurry (S70).

[0097] The method of manufacturing a separator for an electrochemical device according to one embodiment of the present disclosure may maintain adhesive strength with an electrode during a lamination process and maintain adhesive strength after activation of a battery to improve rigidity or prevent bending of a pouch type battery.

[0098] According to one embodiment of the present disclosure, the method for manufacturing a separator for an electrochemical device includes mixing a slurry for coating containing a third polymer binder and inorganic particles (S10). As described above, by mixing a slurry for coating containing a third polymer binder and inorganic particles (S10), a coating can be easily formed on the separator.

[0099] According to one embodiment of the present disclosure, the slurry for the coating can be provided by dispersing the third polymer binder in water (which is a suitable dispersion medium) to make a polymer emulsion. Alternatively, the slurry for the coating can be provided by dissolving the third polymer binder in water (which is a suitable solvent) to make a polymer solution. As described above, by providing a slurry for the coating via dispersing or dissolving the third polymer binder in a suitable dispersion medium or solvent to make a polymer emulsion or polymer solution, the pollutants generated during the manufacturing process can be minimized.

[0100] According to one embodiment of the present disclosure, inorganic particles can be added and dispersed in a polymer emulsion or a polymer solution. According to one embodiment of the present disclosure, the content ratio of the inorganic particles to the third polymer binder is about 95:5, and is appropriately adjusted considering the thickness, pore size and porosity of the coating finally manufactured.

[0101] According to one embodiment of the present disclosure, a method of manufacturing a separator for an electrochemical device includes providing a coating layer by applying a slurry for a coating layer on at least one surface of a porous polymer substrate and drying the slurry ( S30 ).

[0102] According to one embodiment of the present disclosure, a method for manufacturing a separator for an electrochemical device includes applying a slurry for coating on at least one surface of a porous polymer substrate. As described above, by including applying a slurry for coating on at least one surface of a porous polymer substrate, the coating can be formed with a single application, and due to the separation between inorganic particles and polymer binder particles, the portion of the slurry for coating close to the porous polymer substrate contains excess inorganic particles, and the portion of the slurry for coating facing the porous polymer substrate contains excess polymer binder particles. Therefore, the bonding strength with the adhesive layer can be improved and the porosity of the separator can be improved.

[0103] According to one embodiment of the present disclosure, the method for applying the slurry for coating to the surface of the porous polymer substrate is not particularly limited to any one method, and a typical method known in the art can be used. For example, various methods such as dip coating, die coating, roller coating, comma coating, and combinations thereof can be used.

[0104] According to one embodiment of the present disclosure, a method for manufacturing a separator for an electrochemical device includes providing a coating by drying a slurry for coating. As described above, by providing a coating by drying a slurry for coating, damage to the coating can be minimized and a dispersion medium or solvent contained in the slurry can be easily removed.

[0105] According to one embodiment of the present disclosure, the drying process appropriately sets time conditions to minimize the occurrence of surface defects of the coating. For drying, a drying auxiliary device such as a drying oven or hot air may be used within an appropriate range.

[0106] According to one embodiment of the present disclosure, the method for manufacturing a separator for an electrochemical device includes mixing a slurry for an adhesive layer including a second polymer binder (S50). As described above, by including mixing a slurry for an adhesive layer including a second polymer binder (S50), the adhesive layer can be easily formed on the separator.

[0107] According to one embodiment of the present disclosure, the slurry for the adhesive layer can be provided by dispersing the second polymer binder in water (which is a suitable dispersion medium) to make a polymer emulsion. Alternatively, the slurry for the adhesive layer can be provided by dissolving the second polymer binder in water (which is a suitable solvent) to make a polymer solution. As mentioned above, by providing the slurry for the adhesive layer via dispersing or dissolving the second polymer binder in a suitable dispersion medium or solvent to make a polymer emulsion or a polymer solution, the pollutants generated during the manufacturing process can be minimized.

[0108] According to one embodiment of the present disclosure, other ingredients may be added and dispersed into the polymer emulsion or polymer solution. According to one embodiment of the present disclosure, the content ratio of the second polymer binder to the other ingredients is 45:55, and is appropriately adjusted considering the thickness and bonding strength of the adhesive layer finally manufactured.

[0109] According to one embodiment of the present disclosure, a method of manufacturing a separator for an electrochemical device includes providing an adhesive layer by applying slurry for an adhesive layer on one surface of a coating layer and drying the slurry ( S70 ).

[0110] According to one embodiment of the present disclosure, a method for manufacturing a separator for an electrochemical device includes applying a slurry for an adhesive layer on one surface of a coating layer. As described above, by including applying the slurry for an adhesive layer on one surface of the coating layer, the adhesive layer can be formed with a single application, and in the slurry for the adhesive layer, a portion of the slurry for the adhesive layer close to the coating layer contains an excess of other components containing an acrylic-based binder, and a portion of the slurry for the adhesive layer facing the coating layer contains an excess of a second polymer binder, and thus the bonding strength with the silicon-based negative electrode can be improved.

[0111] According to one embodiment of the present disclosure, the method for applying the slurry for the adhesive layer to the surface of the coating is not particularly limited to any one method, and typical methods known in the art can be used. For example, various methods such as dip coating, die coating, roller coating, comma coating, and combinations thereof can be used.

[0112] According to one embodiment of the present disclosure, a method for manufacturing a separator for an electrochemical device includes providing an adhesive layer by drying a slurry for an adhesive layer. As described above, by providing an adhesive layer by drying a slurry for an adhesive layer, damage to the adhesive layer can be minimized and a dispersion medium or solvent contained in the slurry can be easily removed.

[0113] According to one embodiment of the present disclosure, the drying process appropriately sets time conditions to minimize the occurrence of surface defects of the adhesive layer. For drying, a drying auxiliary device such as a drying oven or hot air may be used within an appropriate range.

[0114] According to one embodiment of the present disclosure, the separator 100 is manufactured as an electrochemical device by the following lamination process: wherein the separator 100 is inserted between the silicon-based negative electrode and the positive electrode and combined by applying heat and / or pressure. In one embodiment of the present disclosure, the lamination process can be carried out by a rolling device including a pressure roller pair. That is, interlayer bonding can be achieved by sequentially stacking the silicon-based negative electrode, separator and positive electrode and embedding the silicon-based negative electrode, separator and positive electrode between the pressure rollers. In this case, the lamination process can be carried out by hot pressing.

[0115] One embodiment of the present disclosure provides an electrochemical device including a positive electrode, a silicon-based negative electrode, and a separator interposed between the positive electrode and the silicon-based negative electrode.

[0116] An electrochemical device according to one embodiment of the present disclosure may suppress volume expansion and corresponding degradation of life characteristics due to charge and discharge of a silicon-based active material, and improve stability.

[0117] In the present disclosure, an electrochemical device is a device for converting chemical energy into electrical energy through an electrochemical reaction, and is a concept covering primary batteries and secondary batteries. In this specification, a secondary battery can be charged and discharged, and refers to a lithium secondary battery, a nickel-cadmium battery, a nickel-hydrogen battery, etc. A lithium secondary battery uses lithium ions as an ion conductor, and may include, for example, a non-aqueous electrolyte secondary battery containing a liquid electrolyte, an all-solid-state battery containing a solid electrolyte, a lithium polymer battery containing a gel polymer electrolyte, a lithium metal battery using lithium metal as a negative electrode, etc., but is not limited thereto.

[0118] According to one embodiment of the present disclosure, the adhesive layer included in the separator is disposed on the silicon-based negative electrode. As described above, by disposing the adhesive layer included in the separator on the silicon-based negative electrode, the volume expansion and deterioration of the life characteristics of the silicon-based active material due to charging and discharging can be suppressed, and the stability can be improved.

[0119] According to one embodiment of the present disclosure, the positive electrode includes a positive electrode current collector and a positive electrode active material layer including a positive electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. The positive electrode active material may be one or more of the following: layered compounds such as lithium manganese composite oxides (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), or lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; having the chemical formula Li 1+x Mn 2-x O4 (wherein x is in the range of 0 to 0.33) lithium manganese oxides, such as LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; represented by the chemical formula LiNi 1-x M x O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3) Ni-site type lithium nickel oxides; represented by the chemical formula LiMn 1-x M x O2 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn) lithium manganese composite oxides; LiMn2O4 in which part of Li in the chemical formula is replaced by alkaline earth metal ions; disulfide compounds; and Fe2(MoO4)3.

[0120] According to one embodiment of the present disclosure, the negative electrode includes a negative electrode current collector and a negative electrode active material layer including a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. The negative electrode active material may include one or more silicon-based negative electrode active materials selected from Si, SiO x (0 < x < 2), Si-Y alloy, and Si-C composite material. In addition, the negative electrode may further contain one or more compounds selected from the following as the negative electrode active material: lithium metal oxides; carbon such as non-graphitizable carbon and graphite carbon; metal composite oxides such as Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me1-x Me y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Group 1, Group 2 and Group 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides.

[0121] According to one embodiment of the present disclosure, the conductive material can be any one selected from graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whiskers, conductive metal oxides, activated carbon, and polyphenylene derivatives, or a mixture of two or more thereof. More specifically, the conductive material can be one or a mixture of two or more selected from natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.

[0122] According to one embodiment of the present disclosure, the current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used.

[0123] According to one embodiment of the present disclosure, the negative electrode active material layer can further contain a binder resin. As the binder resin, polymers commonly used in electrodes in the art can be used. Non-limiting examples of the binder resin further contained in the negative electrode active material layer can include polyvinylidene fluoride-copoly-hexafluoropropylene, polyvinylidene fluoride-copoly-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-copoly-vinyl acetate, poly(ethylene oxide), polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, etc., but are not limited thereto.

[0124] According to one embodiment of the present disclosure, the binder resin included in the positive electrode active material layer can be a polymer commonly used in electrodes in the art. Non-limiting examples of the binder resin further included in the positive electrode active material layer can include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, etc., but are not limited thereto.

[0125] According to one embodiment of the present disclosure, the positive electrode slurry for manufacturing the positive electrode active material layer may include a dispersant, and the dispersant may be a pyrrolidone-based compound. Specifically, the positive electrode slurry may be N-methylpyrrolidone (HPD-01, LG Chemical).

[0126] According to one embodiment of the present disclosure, the content of the dispersant contained in the positive electrode slurry may be greater than 0 parts by weight and 0.5 parts by weight or less relative to 100 parts by weight of the positive electrode slurry. Specifically, the content of the dispersant contained in the positive electrode slurry may be greater than 0.05 parts by weight and 0.4 parts by weight or less relative to 100 parts by weight of the positive electrode slurry.

[0127] According to one embodiment of the present disclosure, the negative electrode slurry for manufacturing the negative electrode active material layer may include a dispersant, and the dispersant may be a CMC dispersant (SWCNT, Ocsial, Tuball dispersion).

[0128] According to one embodiment of the present disclosure, the content of the dispersant contained in the negative electrode slurry may be in the range of greater than 0 parts by weight and 1.0 parts by weight or less relative to 100 parts by weight of the negative electrode slurry. Specifically, the content of the dispersant contained in the negative electrode slurry may be in the following ranges: 0.1 parts by weight or more and 0.9 parts by weight or less, 0.2 parts by weight or more and 0.8 parts by weight or less, 0.3 parts by weight or more and 0.7 parts by weight or less, or 0.4 parts by weight or more and 0.6 parts by weight or less relative to 100 parts by weight of the negative electrode slurry.

[0129] According to one embodiment of the present disclosure, a battery may be manufactured by embedding the electrochemical device provided as described above into a suitable housing and injecting an electrolyte solution.

[0130] According to one embodiment of the present disclosure, the electrolyte solution is + B -Salts of the same structure dissolve or dissociate in organic solvents, where A + Including alkali metal cations such as Li + 、Na + , K + , or a combination thereof, and B - Including anions such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 - ions composed of, or a combination thereof, the organic solvent is composed of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof, but is not limited thereto.

[0131] One embodiment of the present disclosure provides a battery module, including a battery including an electrochemical element as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include: an electric tool operated by electricity supplied by a full electric engine, an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), etc., an electric two-wheeled vehicle including an electric bicycle (E-bike) and an electric scooter (E-scooter), an electric golf cart, a power storage system, etc., but are not limited thereto.

[0132] Embodiments of the invention

[0133] Hereinafter, in order to specifically describe the present disclosure, the present disclosure will be described in detail by way of examples. However, the embodiments according to the present disclosure can be modified into various other forms, and the scope of the present disclosure should not be interpreted as being limited to the embodiments to be described below. The embodiments in the specification are provided to more completely describe the present disclosure to those skilled in the art.

[0134] <Example 1>

[0135] <Manufacturing of Separator>

[0136] A porous polymer substrate (about 10 μm total thickness, 40% porosity by volume) was provided.

[0137] A slurry for coating (35 wt % solid concentration) was provided by adding and dispersing an acrylic binder (Toyo, CSB-140, glass transition temperature of -25°C) having a particle size of 150 nm as a third particulate polymer binder, a polyacrylic acid (PAA) dispersant (Dow chemical, CK-702), a wetting agent (BYK, BYK-348) and inorganic particles (Al2O3, particle size of 500 nm) into water. The weight ratio of the third polymer binder to the inorganic particles was 4.6:95.4.

[0138] The slurry for coating was applied on both surfaces of the porous polymer substrate by a bar coating method using a doctor blade, and the slurry was dried with wind at 50° C. using a hot air gun to form a coating layer having a thickness of 1.5 μm on each of the two surfaces.

[0139] A slurry (5 wt % solid concentration) for an adhesive layer was provided by adding and dispersing a solution type PAM-based binder (Miwon, SBS-04) as a second polymer binder, styrene-butyl acrylate (LG Chemical, ADS-11, glass transition temperature 40° C.) as an acrylic-based binder having a particle size of 500 nm, and a polyacrylic acid (PAA) dispersant (Dow chemical company, CK-702) into water. The weight ratio of the particles of the second polymer binder to the other components was 45:55.

[0140] A separator having a total thickness of 14 μm was manufactured by applying slurry for adhesive layer on both surfaces of the coating layer by bar coating using a doctor blade and drying the slurry with wind at 50° C. using a heat gun to form adhesive layers having a thickness of 0.5 μm on both surfaces thereof.

[0141] <Manufacturing of Electrochemical Device>

[0142] 1) Manufacturing of positive electrode

[0143] By 0.8 Mn 0.1 Co 0.1O2), a conductive material (LBCNT, BT1003M, LG Chemical), a dispersant (N-methylpyrrolidone, HPD-01, LG Chemical) and a PVDF binder resin (KF9700, Solvay) were mixed with NMP in a weight ratio of 97.5:0.7:0.14:1.66 to provide a slurry for a positive electrode active material layer having a concentration of 76.5 wt % of the remaining components except NMP. Next, a positive electrode active material layer having a thickness of 4.52 mAh / cm was prepared by applying the slurry on the surface of an aluminum film (12 μm thick) and drying the slurry. 2 The positive terminal of the load.

[0144] 2) Manufacturing of negative electrode

[0145] Silicon particles (Elkem, M702), a PAM-based binder (Arakawa, BUH0452), a conductive material (Imerys, SFG-6L), a conductive material (SWCNT, Ocsial, Tuball dispersion) and a CMC dispersant (SWCNT, Ocsial, Tuball dispersion) were mixed with water in a weight ratio of 80:9.4:9.6:0.4:0.6 to provide a slurry for a negative active material layer having a concentration of 25 wt % of the remaining components except water. Next, a 8 mAh / cm2 film was prepared by applying the slurry on the surface of a copper thin film (having a thickness of 8 μm) and drying the slurry. 2 The negative electrode of the negative electrode load.

[0146] <Comparative Example 1>

[0147] <Manufacturing of Separator>

[0148] In the same manner as in Example 1, a separator was produced.

[0149] <Manufacturing of Electrochemical Device>

[0150] An electrochemical device was manufactured in the same manner as in Example 1, except that an SBR binder (LG Chemical, M37) was used instead of the PAM-based binder when manufacturing the negative electrode in Example 1.

[0151] <Comparative Example 2>

[0152] <Manufacturing of Separator>

[0153] A separator was manufactured in the same manner as in Example 1, except that LBG-4430LX (Arkema, particle size of 250 mm) was used instead of the PAM-based binder in the adhesive layer.

[0154] <Manufacturing of Electrochemical Device>

[0155] In the same manner as in Example 1, an electrochemical device was manufactured.

[0156] <Comparative Example 3>

[0157] <Manufacturing of Separator>

[0158] A separator was manufactured in the same manner as in Example 1, except that LBG-4430LX (Arkema, particle size of 250 mm) was used instead of the PAM-based binder in the adhesive layer.

[0159] <Manufacturing of Electrochemical Device>

[0160] An electrochemical device was manufactured in the same manner as in Example 1, except that when the negative electrode in Example 1 was manufactured, an SBR binder (LG Chemical, M37) was used instead of the PAM-based binder.

[0161] <Comparative Example 4>

[0162] <Manufacturing of Separator>

[0163] In the same manner as in Example 1, a separator was produced.

[0164] <Manufacturing of Electrochemical Device>

[0165] In Example 1, a slurry for a negative electrode active material layer having a concentration of 50 wt % of the remaining components except water was provided by mixing graphite (artificial graphite / natural graphite blend, P20T / LSN-1, Zichen / BTR), SBR binder (LG Chemical, M37), conductive material (carbon black, Super-C65), and dispersant (CMC DAICEL2200, DAICEL, Japan) with water in a weight ratio of 80.3 / 19.7:2.3:1.05:0.5. Next, an electrochemical device was manufactured in the same manner as in Example 1, except that the slurry was applied on the surface of a copper thin film (thickness of 6 μm) and dried, and a 5.5 mAh / cm 2 Specifically, unlike Example 1, the negative electrode was manufactured by using graphite as the negative electrode active material and using an SBR binder (LG Chemical, M37) instead of a PAM-based binder.

[0166] <Experimental Example 1: Air Permeability of Separator>

[0167] Air permeability represents the time for 100cc of air to penetrate an object (such as a separator and a porous polymer substrate) whose air permeability time is to be measured, and can use seconds / 100cc as a unit. Air permeability can be represented by a Gurely value, etc. In the present disclosure, air permeability is measured based on JIS P8117.

[0168] <Experimental Example 2: Dry Adhesion Strength between Negative Electrode and Separator>

[0169] The sample was prepared by laminating the negative electrode and the separators in the embodiments and comparative examples provided by cutting the separators of the embodiments and comparative examples into 70 mm (length) × 25 mm (width) using a press under the conditions of 60°C, 6.5 MPa and 1 second. The provided sample was fixedly attached to a glass plate using a double-sided tape, and in this case, the negative electrode was set to face the glass plate. The separator portion of the sample was peeled off at an angle of 180° at a rate of 150 mm / min at 25°C, and the bonding strength of the negative electrode of the embodiment and comparative example was measured.

[0170] <Experimental Example 3: Wet Adhesion Strength between Negative Electrode and Separator>

[0171] The sample was prepared by laminating the negative electrode and the separators in the embodiments and comparative examples provided by cutting the separators of the embodiments and comparative examples into 70 mm (length) × 25 mm (width) using a press under the conditions of 60 ° C, 6.5 MPa and 1 second. The provided sample was added to the battery case together with the electrolyte solution and kept for 4 hours to impregnate the sample with the electrolyte solution. An electrolyte solution of LiPF6 with a concentration of 1M and a mixture of ethylene carbonate and ethyl methyl carbonate was used. Then, the sample was taken out of the case and fixedly attached to the glass plate using double-sided tape, and in this case, the negative electrode was set to face the glass plate. The separator portion of the sample was peeled off at an angle of 90 ° at a rate of 200 mm / min at 25 ° C, and the bonding strength of the negative electrode of the embodiment and comparative example was measured.

[0172] <Experimental Example 4: Swelling Degree of Electrochemical Device>

[0173] A 2Ah-class small full battery was manufactured by laminating the electrochemical devices of the embodiment and the comparative example. The thickness of each battery manufactured as described above in an initial fully discharged state at 25°C was measured by using a vernier ruler. Then, a cycle evaluation was performed at 25°C, and the thickness of the battery was measured at 600 cycles to measure the change in battery thickness before and after the cycle. When the initial battery thickness is T1 and the battery thickness after 600 cycles is T2, the swelling degree of the electrochemical device is calculated according to the following equation 1.

[0174] [Equation 1]

[0175] Swelling degree (%) = (T2-T1) / T1*100

[0176] [Table 1]

[0177]

[0178] Referring to Table 1, it was confirmed that in Example 1 according to one embodiment of the present disclosure, the dry adhesive strength and the wet adhesive strength between the negative electrode and the separator were significantly improved, and the swelling degree of the electrochemical device was excellent.

[0179] In contrast, it was confirmed that in Comparative Examples 1 to 3, since the PAM-based binder was not included in the negative electrode or the binder layer, the bonding strength between the negative electrode and the separator was rapidly reduced compared to Example 1. In addition, it was found that the swelling degree of the electrochemical device was also higher than that of the electrochemical device of Example 1.

[0180] In Comparative Example 4, it was confirmed that graphite was used instead of a silicon-based negative electrode active material as the negative electrode active material, and the negative electrode did not include a PAM-based binder, and thus the bonding strength between the negative electrode and the separator was rapidly reduced compared to Example 1. However, in Comparative Example 4, it was confirmed that the swelling degree of the electrochemical device was excellent compared to Example 1 because graphite, which does not expand in volume during charge and discharge, was used as the negative electrode active material.

[0181] Therefore, since the separator of the electrochemical device according to one embodiment of the present disclosure includes an adhesive layer disposed between the silicon-based negative electrode and the coating layer, and the silicon-based negative electrode and the adhesive layer each contain a polyacrylamide (PAM)-based binder, the bonding strength with the silicon-based negative electrode can be improved, and the swelling of the electrochemical device to which the silicon-based negative electrode is applied can be suppressed, thereby improving the stability of the electrochemical device.

[0182] [Explanation of Reference Numerals]

[0183] 100: Separators for electrochemical devices

[0184] 110: Porous polymer substrate

[0185] 130: Coating

[0186] 150: Adhesive layer

Claims

1. A separator for an electrochemical device, comprising a binder layer disposed facing a silicon-based negative electrode, wherein the silicon-based negative electrode comprises a silicon-based negative electrode active material and a first polymer binder, The adhesive layer comprises a second polymeric binder, and The first polymer binder and the second polymer binder are each polyacrylamide (PAM) based binders. 2 . The separator for an electrochemical device according to claim 1 , wherein a content of the first polymer binder is 12 parts by weight or less relative to 100 parts by weight of the silicon-based negative electrode. 3 . The separator for an electrochemical device according to claim 1 , wherein the content of the second polymer binder is 50 parts by weight or less relative to 100 parts by weight of the adhesive layer.

4. The separator for an electrochemical device according to claim 1, wherein the silicon-based negative electrode active material is one or more selected from Si, SiO x (0 < x < 2), Si-Y alloy, and Si-C composite material, and Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, but is not Si.

5. The separator for an electrochemical device according to claim 1, further comprising: a porous polymer substrate; a coating disposed on at least one surface of the porous polymer substrate; and An adhesive layer is disposed between the silicon-based negative electrode and the coating. 6 . The separator for an electrochemical device according to claim 5 , wherein the coating layer comprises inorganic particles and a third polymer binder. 7 . The separator for an electrochemical device according to claim 6 , wherein an average particle diameter D50 of the inorganic particles is in the range of 0.3 μm or more and 1.0 μm or less. 8 . The separator for an electrochemical device according to claim 6 , wherein the third polymer binder is an acrylic-based binder, a polyvinylidene-based binder, or a combination thereof. 9 . The separator for an electrochemical device according to claim 1 , wherein the adhesive layer has a dry adhesive strength of 50 gf / 25 mm or more. 10 . The separator for an electrochemical device according to claim 1 , wherein a wet adhesive strength of the adhesive layer is in the range of 10 gf / 25 mm or more and 30 gf / 25 mm or less.

11. An electrochemical device comprising: positive electrode; Silicon-based anode; and the separator according to claim 1 interposed between the positive electrode and the silicon-based negative electrode.

Citation Information

Patent Citations

  • Moving robot

    KR1020230052786A